Biogeochemical implications of chemosynthetic communities on the evolution of authigenic carbonates. (August 2020) - Xi, Shichuan; Zhang, Xin; Luan, Zhendong; Du, Zengfeng; Li, Lianfu; Wang, Bing; Lian, Chao; Yan, Jun
Abstract: Hydrocarbon seepage in cold seeps provides an appropriate environment for chemosynthetic communities to arise and for authigenic carbonates to form. To study the relationships between the chemosynthetic communities and underlying authigenic carbonates, extensive in situ Raman measurements were conducted on the fluids, chemosynthetic communities, and authigenic carbonates found at the Formosa Ridge (Site F) in the South China Sea. Interestingly, the in situ Raman spectra of the authigenic carbonates indicated the highest crystallinity in the fauna-rich area. Scanning electron microscopy and X-ray diffraction analyses of the samples supported the conclusion that the aragonite in the fauna-rich area is more regular than that in the desert area. The in situ Raman spectra suggested that the fluids with relatively low salinity and low sulfate concentrations in the bottom of the chemosynthetic communities can buffer the erosion of underlying authigenic carbonates via the salt effect. In addition, the aragonite content decreased, while the quartz content increased from the fauna-rich area to the desert area (i.e., with increasing distance from the seepage vent). Authigenic aragonite exhibited a negative correlation with terrigenous quartz in the cold seep. The results indicate that changes in chemosynthetic communities have biogeochemical implications on the evolution of authigenic carbonates. Finally, we built a distribution model of the present chemosynthetic communities and underlying authigenic carbonates at Site F, based on systematic in situ Raman measurements and laboratory analyses. This study provides new insights into the evolution of authigenic carbonates based on differences in the spatial distribution of chemosynthetic communities in the seepage system. Highlights: The aragonite in authigenic carbonates decreases gradually from fauna-rich area to desert area. The terrigenous quartz and authigenic aragonite show a negative correlation in the seepage system. The in situ Raman spectra reveal that low-salinity and low-sulfate fluid buffer the erosion of authigenic carbonate.